2017
DOI: 10.1017/wsc.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of 2,4-D Uptake, Translocation, and Metabolism in Non–AAD-1 Transformed and 2,4-D–Resistant Corn

Abstract: The Enlist™ traits provide 2,4-D resistance in several crops. Though corn is naturally tolerant to 2,4-D, the engineered trait conferred by the aryloxyalkanoate dioxygenase-1 (AAD-1) enzyme provides enhanced 2,4-D tolerance and confers resistance to the graminicide herbicide family, the aryloxyphenoxypropionates. The objectives of this research were 2-fold: (1) measure and compare uptake, translocation, and metabolism of 2,4-D in Enlist™ (E, +AAD1) and non–AAD-1 transformed (NT, −AAD1) isogenic corn hybrids; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Significance at p < 0.05 and p < 0.01 levels denoted by * and **, respectively. dioxygenase-1 (AAD-1) enzyme, which results in increased 2,4-D and aryloxyphenoxypropionate metabolism (Anonymous 2012;Ruen et al 2017;Skelton et al 2017). It has been suggested that the introduction of these new technologies will significantly increase 2,4-D use in corn and other crops (Peterson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Significance at p < 0.05 and p < 0.01 levels denoted by * and **, respectively. dioxygenase-1 (AAD-1) enzyme, which results in increased 2,4-D and aryloxyphenoxypropionate metabolism (Anonymous 2012;Ruen et al 2017;Skelton et al 2017). It has been suggested that the introduction of these new technologies will significantly increase 2,4-D use in corn and other crops (Peterson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is an unconventional approach to this type of tests, that can provide insights into the metabolic changes that do not produce visible modifications of the plants. Both 2,4-D plant intake and metabolites of this compound have been reported in the literature [38][39][40]. The dried plants were ground and a methanolic extract was prepared combining two methods described in literature [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…This increase in ethylene biosynthesis is a physiological indicative that the herbicide has caused effects that could lead to the plant death (Song, 2013). Another important factor is the occurrence of adequate temperature and relative humidity in the morning (Table 1), providing greater absorption and translocation of 2,4-D (Peterson et al, 2016;Skelton et al, 2017).…”
Section: Dose (G Ae or Ai Ha -1 ) Herbicidesmentioning
confidence: 99%